Caldic Collectie : Imagine, you are standing here in front of me - Alexander, Brooke; van Caldenborgh, Joop; Dercon, Chris; de Goede, Jannet; Groys, Boris; Lütticken, Sven; Museum Boijmans Van Beuningen, Rotterdam (Rotterdam : NAI, 2002)
Broodthaers, Marcel ; McCollum, allan ; Spoerri, Daniel ; Vercruysse, Jan ; Manzoni, Piero ; Duchamp, Marcel ; Bijl, Guillaume ; ExpoHenK ; Opie, Julian ; Grigely, Joseph ; Zwakman, Edwin ; Warhol, Andy ; Scholte, Rob ; Wool, Christopher ; Kruger, Barbara ; Prince, Richard ; Koons, Jeff ; Artschwager, Richard : etc.
Caldic Collectie, Museum Boijmans Van Beuningen, Rotterdam, 23 november 2002 tot en met 2 februari 2003
Nederlands
kunstcatalogus